2014
DOI: 10.1177/0363546514550982
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial Versus Tibial Inlay Techniques for Posterior Cruciate Ligament Reconstruction

Abstract: Clinical and radiographic outcomes between the 2 PCL reconstruction techniques were comparable. Osteoarthritis was observed in patients, with a significant proportion presenting loss of joint space. Examined factors, excluding meniscectomy, were not correlated with the development of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 32 publications
1
71
0
2
Order By: Relevance
“…9 In a study by Fanelli et al 10 no difference in clinical outcomes was appreciated between single-and double-bundle PCL reconstruction techniques.…”
Section: Discussionmentioning
confidence: 96%
“…9 In a study by Fanelli et al 10 no difference in clinical outcomes was appreciated between single-and double-bundle PCL reconstruction techniques.…”
Section: Discussionmentioning
confidence: 96%
“…On the tibia specimens, the native PCL footprint was identified before the PCL fibers were removed, leaving the remnants of the fibrous attachments intact. The Achilles tendon autograft was then harvested.…”
Section: Methodsmentioning
confidence: 99%
“…The transtibial technique is a popular technique of PCL reconstruction. Although the transtibial technique has the advantages of patient positioning and lower technical difficulty, the “killer turn” has frequently been documented as a primary drawback of this technique. Given the anatomy of the tibial posterior cortex and the direction of tibial and femoral tunnels, there is a sharp angle of the graft at the inlet of the proximal tibial tunnel, which is referred as the “killer turn” after transtibial PCL reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies with long follow-up reported that degenerative changes occur mainly in the medial and patellofemoral compartments,38 39 Kim et al 40 were unable to define the overall prevalence, location or predictors of OA in a systematic review.…”
Section: Mechanism Of Injury Incidence Demographics and Natural Hismentioning
confidence: 99%